2017
DOI: 10.21815/jde.016.019
|View full text |Cite
|
Sign up to set email alerts
|

Dental School Faculty Attitudes Toward Dental Therapy: A Four‐Year Follow‐Up

Abstract: This study is a follow-up to a 2010 study at one U.S. dental school that found faculty attitudes toward the dental therapy model were mixed and there was a clear divide in attitudes between faculty members who were full-time educators and part-timers who also practiced outside the educational institution. The aim of this study was to determine faculty attitudes toward and perceptions of the dental therapy model at the same school four years after implementation of the dental therapy program. The identical ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Oregon pilot projects are under evaluation, and preliminary results in both Oregon and Washington, as reported by stakeholders, have also been positive. In Minnesota, the evidence of patient and provider acceptability, education quality, practice capacity, economic benefit, and health improvements is also robust 18,51,58–64. Dental safety net facilities have been great supporters and early employers of DTs in Minnesota.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Oregon pilot projects are under evaluation, and preliminary results in both Oregon and Washington, as reported by stakeholders, have also been positive. In Minnesota, the evidence of patient and provider acceptability, education quality, practice capacity, economic benefit, and health improvements is also robust 18,51,58–64. Dental safety net facilities have been great supporters and early employers of DTs in Minnesota.…”
Section: Resultsmentioning
confidence: 99%
“…In Minnesota, the evidence of patient and provider acceptability, education quality, practice capacity, economic benefit, and health improvements is also robust. 18,51,[58][59][60][61][62][63][64] Dental safety net facilities have been great supporters and early employers of DTs in Minnesota. A survey of 32 safety net providers reported that clinical directors overwhelmingly (77%) supported the dental therapy provider model.…”
Section: Educational Capacity For Training Dental Therapistsmentioning
confidence: 99%
“…Increasing the number of dentists who see financial and clinical advantages from employing DTs may make organized dentistry, a traditional opponent of dental therapy, into an unexpected advocate. Dentists who work with or train alongside DTs report more favorable attitudes toward these providers, 35 a pattern paralleled by changing physician attitudes towards advanced practice providers in medicine 36 . With continued expansion, the vocal opposition of organized dentistry may fade.…”
Section: The Future Of Dental Therapymentioning
confidence: 99%
“…Ideally, in 20 years these new dental providers will be as common and as accepted in both medicine and dentistry as other primary care providers are in medicine. It is encouraging that a study by Self et al found that, after four years of experience with the dental therapy program at the University of Minnesota, dental faculty members demonstrated greater acceptance of dental therapists and viewed the role of dental therapy more favorably than when the program was first introduced 30 …”
Section: Integration Into the Workforcementioning
confidence: 99%